Epidemiological Analysis of a K. pneumoniae NDM Outbreak in a Temporary Ward for Patients with Primary COVID-19 Infection - Agata Pruss; Klaudia Miładowska; Helena Masiuk; Paweł Kwiatkowski; Joanna Jursa-Kulesza; Bartosz Wojciuk; Stefania Giedrys-Kalemba; Barbara Dołęgowska (Microbiology Research)
The COVID-19 pandemic made the medical community realize how large a problem it would face. The epidemiological situation forced the opening of additional wards, the so-called “COVID wards”, where an increase in the rate of coexisting bacterial infections was observed. We report a hospital outbreak due to New Delhi carbapenemases producing K. pneumoniae clones. Twenty-eight K. pneumoniae strains were analyzed from patients with primary COVID-19 infection. The drug susceptibility of the strains was determined by the diffusion–circulation method and E-test. Phenotypic and PCR methods confirmed the production of carbapenemases. The phylogenetic similarity of the obtained strains was examined using pulsed-field electrophoresis. Most strains were isolated from bronchoalveolar lavage. All isolates obtained were resistant to β-lactams and fluoroquinolones. All strains produced New Delhi carbapenemases and were classified into two genetic clusters, A and B. Eight risk factors for secondary bacterial infection were analyzed. Following an intervention involving hand hygiene, strict contact prevention, and cleaning of the hospital environment and medical devices, this outbreak was successfully brought under control.